Oocyte In Vitro Maturation with Crude Sperm Extract Protein of Bull's Spermatozoa - Bilqis, Bilqis; Rahayu, Sri; Ciptadi, Gatot (The Journal of Experimental Life Science, 2016)
Oocyte In vitro maturation (IVM) is one of the important parts for in vitro fertilization (IVF). The success of oocyte maturation is influenced by the composit ion and the quality of IVM medium. Culture medium which used to IVM not only influences the oocyte process to reach metaphase II and proceed the fertilization, but also influences to developmental of an embryo. Crude sperm extract has high-level protein kinase and contains some sperm proteins. Crude sperm extracts expected as natural maturation medium that can increase the success of In Vitro Maturation (IVM). The characterization of crude sperm extracts profile with sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE). Oocyte maturation is observed in the 26th hour from the first culture. The result of crude sperm extract characterization obtained from the protein with the molecular weight is 176.8, 63.2, 58.4, 55.3, 52.4, 49.7, 44.6, 38.02, 36.03, 34.15 and 26.8 kDa. Oocyte maturation with concentration of crude sperm extract 1.5 µg.mL-1 with 71.6% matures oocyte and oocyte maturation with concentration of crude sperm extract 2.5 µg.mL-1 with 75% matures oocyte. Keywords: Crude Sperm Extract, In Vitro Maturation, Oocyte